2018
DOI: 10.1021/acschemneuro.8b00085
|View full text |Cite
|
Sign up to set email alerts
|

Tyr1-ψ[(Z)CF═CH]-Gly2 Fluorinated Peptidomimetic Improves Distribution and Metabolism Properties of Leu-Enkephalin

Abstract: Opioid peptides are key regulators in cellular and intercellular physiological responses, and could be therapeutically useful for modulating several pathological conditions. Unfortunately, the use of peptide-based agonists to target centrally located opioid receptors is limited by poor physicochemical (PC), distribution, metabolic, and pharmacokinetic (DMPK) properties that restrict penetration across the blood-brain barrier via passive diffusion. To address these problems, the present paper exploits fluorinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 54 publications
(103 reference statements)
0
23
0
Order By: Relevance
“…Moreover, in the specific case of GPCR complexes, CPPs can also determine the trajectory of the peptide disruptor into the membrane [80]. Peptide backbone modification is also an important and widely used approach to improve bioavailability [83,84]. Still another strategy to increase target affinity and cell uptake, as well as to protect against proteolytic degradation, involves stapling, whereby a synthetic brace (staple) introduced between two preestablished sites in the sequence helps to lock the peptide into a specific secondary structure (Figure 2F), thus reducing conformational entropy [85][86][87].…”
Section: Tm Peptides: Challenges and Opportunities To Drug The Undrug...mentioning
confidence: 99%
“…Moreover, in the specific case of GPCR complexes, CPPs can also determine the trajectory of the peptide disruptor into the membrane [80]. Peptide backbone modification is also an important and widely used approach to improve bioavailability [83,84]. Still another strategy to increase target affinity and cell uptake, as well as to protect against proteolytic degradation, involves stapling, whereby a synthetic brace (staple) introduced between two preestablished sites in the sequence helps to lock the peptide into a specific secondary structure (Figure 2F), thus reducing conformational entropy [85][86][87].…”
Section: Tm Peptides: Challenges and Opportunities To Drug The Undrug...mentioning
confidence: 99%
“…Later, Altman et al . reported that Leu‐enkephalin derivatives Tyr 1 ‐ψ[(Z)CF=CH]‐Gly 2 with the second amide bond modified by the fluoroalkene moiety showed improved distribution and metabolic properties [82] …”
Section: Peptide Backbone Modifications and Solid‐phase Synthesis Tec...mentioning
confidence: 99%
“…One of the most viable alternatives to small molecule painkillers is to develop native endogenic peptide pain relievers with enhanced drug-like properties. Various strategies have been developed over the years to produce stable enkephalin and endorphin mimetics (Karad et al, 2017 ; Altman et al, 2018 ; Harris et al, 2019 ). These short peptides contained all the essential pharmacophores of the parent peptide that proved crucial for bioactivity.…”
Section: Introductionmentioning
confidence: 99%